2014
DOI: 10.1186/1744-8069-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Toll like Receptor (TLR)-4 as a Regulator of Peripheral Endogenous Opioid-Mediated Analgesia in Inflammation

Abstract: BackgroundLeukocytes containing opioid peptides locally control inflammatory pain. In the early phase of complete Freund’s adjuvant (CFA)-induced hind paw inflammation, formyl peptides (derived e.g. from Mycobacterium butyricum) trigger the release of opioid peptides from neutrophils contributing to tonic basal antinociception. In the later phase we hypothesized that toll-like-receptor-(TLR)-4 activation of monocytes/macrophages triggers opioid peptide release and thereby stimulates peripheral opioid-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 57 publications
1
43
0
3
Order By: Relevance
“…There are, however, relatively few studies examining the effect of myeloid cell depletion in inflammatory pain, and these show contradictory results. One study showed that local depletion of Mø using clodronate liposomes did not alter pain behavior after intraplantar injection of CFA (56), whereas others have reported that systemic depletion of these cells using clodronate liposomes or an α-CCR2 antibody results in an unexpected increase in mechanical and thermal hypersensitivity after intraplantar injection of carrageenan (70) or CFA (71). The mechanisms suggested for the inferred antinociceptive effects for these cells was that they either secrete β-endorphins (71) or act in the dorsal root ganglia and spinal cord to produce antiinflammatory cytokines like IL-10 (70).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, relatively few studies examining the effect of myeloid cell depletion in inflammatory pain, and these show contradictory results. One study showed that local depletion of Mø using clodronate liposomes did not alter pain behavior after intraplantar injection of CFA (56), whereas others have reported that systemic depletion of these cells using clodronate liposomes or an α-CCR2 antibody results in an unexpected increase in mechanical and thermal hypersensitivity after intraplantar injection of carrageenan (70) or CFA (71). The mechanisms suggested for the inferred antinociceptive effects for these cells was that they either secrete β-endorphins (71) or act in the dorsal root ganglia and spinal cord to produce antiinflammatory cytokines like IL-10 (70).…”
Section: Discussionmentioning
confidence: 99%
“…Наприклад, ІЛ-1β може викликати експресію ФНП-α і ІЛ-6, тоді як ІЛ-18 стимулює про-дукцію ІЛ-17 [2]. Прозапальні цитокіни пригнічують функції гематоенцефалічного бар'єру, опосередкову-ють залучення гематогенних лейкоцитів у мозок та є причиною виникнення болю запального ґенезу [3][4][5][6].…”
Section: вступunclassified
“…Локально впливати на біль, зокрема запального характеру, здатні клітини моноцитар-но-макрофагальної системи завдяки наявності в них опіоїдних пептидів. При активації TLR4 моноцитів/ макрофагів, окрім прозапальних цитокінів, виникає вихід опіоїдних пептидів з останніх, що є одним із важливих механізмів антиноцицептивної системи [5]. Саме тому доцільно вивчити експресію TLR4 в плазмі як маркеру розвитку гіпералгезії в післяопе-раційному періоді.…”
Section: обґрунтування дослідженняunclassified
See 1 more Smart Citation
“…This study has demonstrated that DYN 3-14 blocks LPS-induced TLR4 signalling in HEK-Blue™- This study highlights that TLR4 potentially regulates peripheral endogenous opioid-mediated analgesia in inflammation (56). Opioid agents such as morphine and fentanyl have been shown to inhibit TLR4 signalling through non-competitive binding with LPS (54).…”
Section: Dyn 3-14 Inhibits Lps-induced Tlr4 Activation In Hek-blue™-hmentioning
confidence: 69%